The association between awkward working posture and low back disorders in farmers: a systematic review. Issue 1 (2nd January 2019) - Khan, Muhammad Idrees; Bath, Brenna; Boden, Catherine; Adebayo, Olugbenga; Trask, Catherine
ABSTRACT: Background : Low back disorders (LBD) are the most common musculoskeletal problem among farmers, with higher prevalence than other occupations. Although studies of the general population have shown an association between LBD and awkward working posture, farmers have unique work context and exposures that may modify this relationship. This review aimed to 1) identify published research studies investigating posture as a risk factor for LBD in farmers/agricultural workers, and 2) determine the strength of the relationship between postural exposure and LBD risk of bias assessment. Method : Comprehensive electronic searches of Medline, Web of Science, CINAHL, SCOPUS, PubMed, and EMBASE were carried out with combined conceptual groups of search terms for 'farming' and 'LBD.' After screening, data were extracted to summarize the study design, sample characteristics, exposure assessment methods, LBD risk factors, demographic information, data collection methods, farm commodities, job context, and sampling strategy. Data were synthesized to determine the weight of evidence for awkward working posture as a risk factor for LBD among farmers. Results : Nine studies were included in this review. All studies used self-report; there were no field-based studies including direct measurement of awkward posture. There was diversity in exposure definition, exposure assessment, LBD definition, worker characteristics, and analytical approaches. There was evidence to support association between awkward working posture and LBD among farmers. Conclusion : Despite the diversity, the weight of evidence supported a relationship between awkward posture and LBD. Well-designed epidemiological studies with quantitative physical workload assessments, consistent and valid LBD definitions, and longitudinal designs are recommended to clarify the relationship between awkward posture and LBD.